Operations Research: from Strategy to Meaningful Learning - Perez Montero, Ellien Lorena; Ramirez, José Bernardo (TECCIENCIA, 2019)
This paper examines the use of information communication technology (ICT) for meaningful learning in the undergrad course of Operation Research taken in the fourth year of Industrial Engineering at University Corporation of Huila, CORHUILA. Over the past year, students that took Operation Research showed difficulty in understanding the concepts, answering tests which reflected on the final grade. Therefore, it was necessary to examine the application of ICT tools in the classroom. To show the effectiveness of the proposed methodology, it was designed a quasi-experimental research with a sample of 68 students distributed in two groups. The Control group was thought using the traditional methodology; whereas the Experimental group had access to ICT tools for learning. The results showed a significant relationship between the academic success of the Experimental group and the ICT tools applied; moreover, better grading compared to the Control group.